Serialization of Ọbasa’s Poems in The Yorùbá News - Tolulope Ibikunle (Yoruba Studies Review)
Every newspaper has its form, structure, and pattern. The Yorùbá News published between 1924-1945 was not an exception, as it comprised of different contents ranging from the editorial opinion to home news, gossip, adverts, and serialization of different forms of narratives. D.A. Ọbasa, the publisher ́ of The Yorùbá News, also published many works of poetry. Ọbasa started the publication of excerpts of his poems in The Yoruba News under the column “Àwọn Akéwì.” Serializing these poems, therefore, means issuing them regularly and consecutively in diferent editions of the newspaper. In the various scholarly engagements with Ọbasa’s works, little or no attention has been given to the serialization of his poems in Te Yorùbá News. The focus of this easy therefore is to fill this gap by highlighting and documenting the serialized poems of Ọbasa in Te Yorùbá News. Trough intertextuality theory, the easy aims at appraising how Ọbasa transfer his knowledge of the Yorùbá oral literature to his readers through his application of oral poetic form from his serialized poems. Tis work will therefore dwell on Intertextuality and its influence on the works of Ọbasa, which will enable us to discuss his creative ability as a cultural activist.